Properties of empty fruit bunches ash (EFBash) concrete / Mohd Amizan Mohamed @ Arifin and Assoc. Prof. Ir. Dr. Kartini Kamaruddin - Mohamed @ Arifin, Mohd Amizan; Kamaruddin, Kartini (Research Management Institute (RMI), 2012)
Agricultural waste material that available to be used as a cement replacement in concrete mix is called Supplementary Cement Materials (SCM). One of the agricultural wastes that has potential to be used is the Empty Fruit Bunches (EFB). The EFBash offers advantages as SCM because it can prevent the environmental degradation and pollution. This ash will be tested with X- Ray Fluorescence Spectrophotometer (XRF) test to determine its chemical composition. The effects of using different percentages of EFBash replacement its compressive strength and durability will also be determined. For this research, the percentages of replacement of EFBash employed to cement (by weight) are 5%, 10%, 15%, 20% and 30%. The EFBash concrete of Grade 30 with 0.5, 0.55, 0.6 and 0.65 w/c ratios will be tested on its compressive strength and durability performance, i.e. by conducting compression test, permeability test and water absorption tests. The data will be taken from different ages i.e. 7, 14, 28, 60, 90 and 120 days. From this research, the optimum mix in achieving compressive strength and also the durability of EFBash concrete will be determined.